Comprehensive characterization of nutritional components in sweetpotato (Ipomoea batatas [L]. Lam.) during long-term post-harvest storage - Zhao, Lingxiao (Journal of plant physiology, 2024)
Copyright © 2024 Elsevier GmbH. All rights reserved.